LARA

Differences

This shows you the differences between two versions of the page.

Link to this comparison view

Both sides previous revision Previous revision
sav07_lecture_22 [2008/05/21 01:17]
vkuncak
sav07_lecture_22 [2015/04/21 17:32] (current)
Line 58: Line 58:
 ==== Semantic ==== ==== Semantic ====
  
-We define the semantic of our syntax recursively by defining each of its elements over a language $L = \lbrace a, \ldots, f_1, \ldots, g_1, \ldots \rbrace$. We first have that : \[[S]] \in H \where $H$ is the Herbrand univers, or "set of all ground terms",​ or also called the "term model"​. As we already saw, it's the set of all possibly constructed trees using language $L$ : \H = \lbrace a, f_1(a, a), f_1(g_1(a, a), a), \ldots \rbrace \]+We define the semantic of our syntax recursively by defining each of its elements over a language $L = \lbrace a, \ldots, f_1, \ldots, g_1, \ldots \rbrace$. We first have that : \begin{equation*} ​[[S]] \in H \end{equation*} ​where $H$ is the Herbrand univers, or "set of all ground terms",​ or also called the "term model"​. As we already saw, it's the set of all possibly constructed trees using language $L$ : \begin{equation*} ​H = \lbrace a, f_1(a, a), f_1(g_1(a, a), a), \ldots \rbrace \end{equation*}
  
 Given that, if the meaning of $v$ is given (i.e. we have $[[v]] = \alpha(v) \subseteq H$), then we can estimate the meaning of our language as following : Given that, if the meaning of $v$ is given (i.e. we have $[[v]] = \alpha(v) \subseteq H$), then we can estimate the meaning of our language as following :
Line 77: Line 77:
 ==== ==== ==== ====
  
-An important property we would like to have in this semantic is a very intuitive one : \[[f^{-1}(f(S_1,​ S_2))]] = [[S_1]] \]+An important property we would like to have in this semantic is a very intuitive one : \begin{equation*} ​[[f^{-1}(f(S_1,​ S_2))]] = [[S_1]] \end{equation*}
 This property is in fact not conserved as we can easily see using a very simple counter-example : This property is in fact not conserved as we can easily see using a very simple counter-example :
-\[[f^{-1}(f(S_1,​ \emptyset))]] = [[f^{-1}(\lbrace f(t_1, t_2) | t_1 \in [[S_1]] \wedge t_2 \in \emptyset \rbrace)]] = [[f^{-1}(\emptyset)]] = \emptyset \]+\begin{equation*} ​[[f^{-1}(f(S_1,​ \emptyset))]] = [[f^{-1}(\lbrace f(t_1, t_2) | t_1 \in [[S_1]] \wedge t_2 \in \emptyset \rbrace)]] = [[f^{-1}(\emptyset)]] = \emptyset \end{equation*}
  
 The correct interpretation of this property is : The correct interpretation of this property is :
Line 143: Line 143:
  
 From this we can deduce, as we defined previously, the following contraints : From this we can deduce, as we defined previously, the following contraints :
-\[\begin{array}[c]+\begin{equation*}\begin{array}[c]
 \left { \lambda_x \right } \subseteq [[\lambda x.x]] \\ \left { \lambda_x \right } \subseteq [[\lambda x.x]] \\
 \left { \lambda_y \right } \subseteq [[\lambda y.y]] \\ \left { \lambda_y \right } \subseteq [[\lambda y.y]] \\
 \lambda_x \subseteq [[\lambda x.x]] \Rightarrow \left (  [[\lambda y.y]] \subseteq [[x]] \wedge [[x]] \subseteq [[\left ( \lambda x.x \right ) \lambda y.y]] \right ) \\ \lambda_x \subseteq [[\lambda x.x]] \Rightarrow \left (  [[\lambda y.y]] \subseteq [[x]] \wedge [[x]] \subseteq [[\left ( \lambda x.x \right ) \lambda y.y]] \right ) \\
 \lambda_y \subseteq [[\lambda x.x]] \Rightarrow \left (  [[\lambda y.y]] \subseteq [[y]] \wedge [[y]] \subseteq [[\left ( \lambda x.x \right ) \lambda y.y]] \right ) \lambda_y \subseteq [[\lambda x.x]] \Rightarrow \left (  [[\lambda y.y]] \subseteq [[y]] \wedge [[y]] \subseteq [[\left ( \lambda x.x \right ) \lambda y.y]] \right )
-\end{array} \]+\end{array} \end{equation*}
  
 Which leads to the following solutions : Which leads to the following solutions :